Xanthogranulomatous cholecystitis: A malignant mimicker - Gangadharan, Vandana; Atla, Bhagyalakshmi; Guruvelli, Sandya Rani; Ravada, Saritha Rani (Indian Journal of Case Reports, 2025)
Xanthogranulomatous cholecystitis (XGC) is a rare, chronic inflammatory disease of the gallbladder (GB) that often mimics GB carcinoma clinically, radiologically, and intraoperatively. Its accurate diagnosis is critical to avoid unnecessary extensive surgery. A 71-year-old female presented with diffuse abdominal pain and intermittent fever for 2 months. Imaging (magnetic resonance cholangiopancreatography and contrast-enhanced computed tomography) revealed irregular thickening of the GB wall with a rent in the fundus and pericholecystic collection, suggesting a neoplastic etiology. A diagnostic laparoscopy with radical cholecystectomy was performed due to high suspicion of carcinoma. Gross examination showed a thickened, ragged GB wall infiltrating into the liver. Histopathology revealed mucosal denudation, subepithelial fibrosis, foamy histiocytes, and chronic inflammatory infiltrates, confirming the diagnosis of XGC. No malignancy was identified. The patient recovered uneventfully and remained asymptomatic at 9-month follow-up. XGC is a benign but aggressive inflammatory condition that can closely resemble GB cancer. Histopathological examination remains the gold standard for diagnosis. Awareness of this entity is essential to guide appropriate surgical management and avoid overtreatment.